Total Quality Management Implementation: A Pragmatic Study of Educational Enhancement in an Islamic School - Fuadi, Fairuz Amin; Andika, Aryan; Arini, Hanifah Nur; Chrisnawati, Rosalia (HEUTAGOGIA: Journal of Islamic Education, 2025)
Quality assurance has become a central concern in the management of modern Islamic educational institutions, highlighting the need for systematic approaches to achieve sustainable standards. This study examines how the implementation of Total Quality Management (TQM) principles supports quality improvement in the learning process at SMP Islam Integral Purwodadi. A descriptive qualitative approach was employed, using in-depth interviews, classroom observations, and document analysis, including student report cards and parent satisfaction surveys. The findings indicate that the school has adopted a customer-focused orientation by prioritizing the needs of students and parents in managerial decision-making. Report card data are utilized to evaluate the curriculum and design teacher training programs. However, the study also identifies challenges such as suboptimal TQM training for new teachers and a quality information system that remains insufficiently integrated. These results suggest that successful TQM implementation requires strong institutional commitment, investment in supportive quality systems, and a sustained culture of continuous improvement. The study recommends strengthening the quality information system and implementing ongoing professional development as key strategies for enhancing institutional performance through TQM.